Serous Cystadenoma of the Pancreas Presenting as a Third Primary Neoplasm - Aydın Şeref Köksal; Aysel Ülker; Mehmet Asıl; Bilge Tunç; Arda Kemal; Metin Şavkılıoğlu; Yusuf Özoğul; Nesrin Turhan (Canadian Journal of Gastroenterology)
Serous cystadenomas are the most common cystic neoplasms of the pancreas. They may occur solely or coexist with other neoplasms. A 10 cm mass involving the body of the pancreas was observed in the computed tomography of a 61-year-old man with a previous history of bladder and prostate carcinoma. Ultrasonography and computed tomography of the mass demonstrated multiple small cysts associated with a central calcified scar. A distal pancreatectomy was performed. Pathological examination confirmed the diagnosis of serous microcystic adenoma. This is the first report of a serous cystadenoma of the pancreas with two metachronous neoplasms. This feature should be kept in mind during the diagnosis and evaluation of patients with serous cystadenoma.